HUBUNGAN PERILAKU DENGAN KEMAMPUAN PERAWAT DALAM MELAKSANAKAN KESELAMATAN PASIEN (PATIENT SAFETY) DI RUANG AKUT INSTALASI GAWAT DARURAT RSUP PROF. DR. R. D. KANDOU MANADO - Lombogia, Angelita; Rottie, Julia; Karundeng, Michael (Universitas Sam Ratulangi, 2016)
Abstract:. Patient Safety is something that is far more important than the efficiency of the treatment, and the attitude with behavior of the nurse have an important role in the patient safety. Aim of the study: to identify the relationship between nurse’s behavior and competence in the practice of patient safety. Methods: design of this study using analytic survey with cross sectional approach. The population are all the nurses who works at the acute emergency room in Prof. Dr. R. D. Kandou Manado Hospital and using purposive sampling that involved 31 nurses. The tools used were in this study are nurses behavior questionnaire sheet and nurse’s competence in the practice of patient safety observation sheet. Result: analysis while using Fisher’s Exact Test, shows that the p value identify patient is 0,043, the p value reduction risk of infection is 0,006 and the p value reduction risk of patient falls is 0,001 using Chi-square. All the p value smaller than the α value is 0,05. Conclusion: there is a relationship between behavior and nurse’s competence in the practice of patient safety at the acute emergency room in Prof. Dr. R. D. Kandou Manado Hospital. Recommendations: the hospital nurses should improve their work discipline and compliance to increase the quality of nursing care which is related to patient safety according to hospital. Keywords : behavior, competence, patient safety. Abstrak: Keselamatan pasien merupakan sesuatu yang jauh lebih penting dari pada sekedar efisiensi pelayanan, dan perilaku dengan kemampuan perawat sangat berperan penting. Tujuan penelitian: mengetahui hubungan perilaku dengan kemampuan perawat dalam melaksanakan patient safety. Metode: desain penelitian ini adalah cross sectional. Populasi pada penelitian ini adalah seluruh perawat yang bekerja di Ruang Akut IGD RSUP Prof. Dr. R. D. Kandou Manado. Teknik pengambilan sampel menggunakan purposive sampling yang melibatkan 31 perawat sebagai responden. Instrument yang digunakan yaitu kuesioner perilaku perawat dan lembar observasi kemampuan perawat tentang keselamatan pasien. Hasil: analisis menggunakan Fisher’s Exact Test dan menunjukkan nilai p pada identifikasi pasien yaitu p=0,037, pada resiko infeksi pasien nilai p=0,005, dan pada resiko pasien jatuh nilai p=0,001 menggunakan Chi-square. Semua nilai p lebih kecil dari nilai α=0,05. Simpulan: terdapat hubungan antara perilaku dengan kemampuan perawat dalam melaksanakan patiet safety di Ruang Akut IGD RSUP Prof. Dr. D. R. Kandou Manado. Saran: bagi rumah sakit lebih meningkatkan mutu pelayanan keperawatan yang berkaitan dengan keselamatan pasien sesuai dengan panduan nasional keselamatan pasien. Kata Kunci : perilaku, kemampuan, patient safety.